Marker-assisted pyramiding of resistance loci to grape downy mildew - Saifert L. (2018)
© 2018, Embrapa.The objective of this work was to use a marker-assisted selection for pyramiding the resistance loci Rpv1 and Rpv3.1 in grapevine (Vitis vinifera), and to evaluate their conferred resistance against Brazilian downy mildew (Plasmopara viticola) isolates. A progeny of 23 plants, segregating for the two resistance loci, was obtained by the cross between the Gf 2000-305-122 and Gf.Ga-52-42 genotypes. The progeny was genotyped with four microsatellite markers and phenotyped for resistance to P. viticola using a bioassay with leaf discs. Six plants containing the Rpv1 and Rpv3.1 pyramided loci were identified by the molecular analysis. Plants harboring the Rpv1 + Rpv3.1, Rpv3.1, and Rpv1 loci showed 12.8, 30.0, and 33.1 sporangiophores per leaf disc, respectively. Plants with no resistance loci showed a dense sporulation. The phenotypic analysis of the expression of the two pyramided loci was only confirmed for four plants that showed the highest resistance level, i.e., mean value of 1.8 sporangiophores. A high-throughput method for pyramiding the Rpv1 and Rpv3.1 loci was developed, which confirmed the increased resistance to P. viticola. The selected elite genetic material shows a high resistance to downy mildew and elevated enological potential for grapevine breeding in Brazil.© 2018, Embrapa.O objetivo deste trabalho foi o emprego da seleção assistida por marcadores moleculares para piramidação dos locos de resistência Rpv1 e Rpv3.1, em videira (Vitis vinifera), e avaliar o nível de resistência conferido por eles contra isolados brasileiros de míldio (Plasmopara viticola). Uma progênie de 23 plantas, com segregação para os dois locos de resistência, foi obtida do cruzamento entre os genótipos Gf2000-305-122 e Gf.Ga-52-42. A progênie foi genotipada com quatro marcadores microssatélites e fenotipada, quanto à resistência a P. viticola, em discos foliares. A análise molecular identificou seis plantas com os locos Rpv1 e Rpv3.1 piramidados. Plantas com os locos Rpv1 + Rpv3.1, Rpv3.1 e Rpv1 apresentaram 12,8, 30,0 e 33,1 esporangióforos por disco foliar, respectivamente. As plantas sem locos de resistência tiveram esporulação densa. A análise fenotípica da expressão dos dois locos piramidados foi confirmada somente para quatro plantas que mostraram o maior nível de resistência, isto é, média de 1,8 esporangióforos. Desenvolveu-se uma metodologia de alto rendimento para a piramidação dos locos Rpv1 e Rpv3.1, que confirmou o aumento da resistência a P. viticola. O material genético superior selecionado apresenta alta resistência ao míldio e elevado potencial enológico para o melhoramento da videira no Brasil.